The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1029/2019wr026867
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Removal Across Ecogeomorphic Zones in Wax Lake Delta, Louisiana (USA)

Abstract: Human activities have increased nitrate export from rivers, degrading coastal water quality. At deltaic river mouths, the flow of water through wetlands increases nitrate removal, and the spatial organization of removal rates influences coastal water quality. To understand the spatial distribution of nitrate removal in a river‐dominated delta, we deployed 23 benthic chambers across ecogeomorphic zones with varying elevation, vegetation, and sediment properties in Wax Lake Delta (Louisiana, USA) in June 2018. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 92 publications
0
34
0
Order By: Relevance
“…2). Work in other systems has shown that network structure can also be used to estimate flux partitioning and the delivery of fluxes at the shore (Tejedor et al, 2015) and that estimation of nutrient and sediment fluxes can be addressed in similar ways (Dong et al, 2020;Knights et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…2). Work in other systems has shown that network structure can also be used to estimate flux partitioning and the delivery of fluxes at the shore (Tejedor et al, 2015) and that estimation of nutrient and sediment fluxes can be addressed in similar ways (Dong et al, 2020;Knights et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…10.1029/2020WR028090 2 of 14 and anthropogenic processes influence water, sediment, and nutrient transport pathways (Knights et al, 2020;Sanks et al, 2020). The USACE analyses (Fisk, 1952;Latimer & Schweitzer, 1951) were based on empirical analyses of extensive datasets.…”
mentioning
confidence: 99%
“…The development of the flow directions algorithms itself provided insights into the nature of river channel network structure in braided rivers and deltas (Schwenk et al, 2020). For deltas specifically, RivGr aph-extracted networks have been used to study how water and sediment are partitioned at bifurcations (Dong et al, 2020), to determine how distance to the channel network plays a controlling role on Arctic delta lake dynamics (Vulis et al, 2020), and to construct a networkbased model of nitrate removal across the Wax Lake Delta (Knights et al, 2020). For braided rivers, RivGraph was used to extract channel networks from hydrodynamic simulations in order to develop the novel "entropic braiding index" (eBI, Tejedor et al, 2019), and a function for computing the eBI (as well as the classic braiding index) for braided rivers is provided in RivGraph.…”
Section: Statement Of Needmentioning
confidence: 99%